: ; Livestock sector in Tajikistan: Problems of sustainable and balanced development - Khojamahmad Umarov (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2019)
– This publication highlights the development of livestock sector in Tajikistan. The paper begins with presentation of macroeconomic aspects of agricultural development pointing at the impact of transitional decline on the development of agricultural sector. At present, the share of agricultural sector in GDP is twice less than in 1990. Although, the growth rate of gross agricultural output after 2000 remains high the 1990 levels for a variety of products have not been reached yet. This applies to a variety of animal products. The development of this industry is characterized by imbalances and unbalanced development. The disproportion between livestock and feed resources is growing rapidly. The fodder capacity of summer and winter pastures decreases each year. Pasture land is degraded, and in many places this becomes irreversible. This requires the transfer of livestock to animal housing systems to give pastures the opportunity for natural restoration of green cover. To this end, the author recommends a reduction in unproductive livestock breeds, the conversion of cattle to stable housing by changing breeds, i.e. herd formations by replacing local unproductive breeds with highly productive meat and dairy breeds. In addition the author recommends to expand area under forage crops and to shift to intensive fodder production.
urn:nbn:de:gbv:3:2-112102
Keywords: 330; livestock sector; pastures; Tajikistan